Relationship Between Trust To Leaders And Employee Performance at PT. X - Aburizal Fatwa Ramli (Yayasan Amerta Insan Unggul, 2024)
Employee performance is a critical determinant of organizational success, and trust in leadership has been identified as a significant factor influencing performance outcomes. This study aims to examine the relationship between trust in leaders and employee performance at PT. X, a family-owned property company in Makassar. A quantitative research design was employed, with a total of 39 employees selected as respondents using proportional random sampling. Trust in leadership was measured using a scale encompassing integrity, competence, consistency, loyalty, and openness, while employee performance was assessed based on task accomplishment, quality, and responsibility. Data were analyzed using Pearson’s correlation coefficient. The results indicate a significant positive relationship between trust in leaders and employee performance, with a correlation coefficient of 0.532 (p = 0.000), categorized as a moderate relationship. Employees who report higher levels of trust in their leaders tend to demonstrate higher performance, confirming previous findings that trust enhances work motivation, commitment, and productivity. These results highlight the importance for leaders to foster and maintain employee trust through transparency, fairness, and competence. The study provides practical implications for human resource management, suggesting that organizations can improve performance outcomes by strengthening the trust between leaders and subordinates. By promoting a trustworthy leadership culture, PT. X can enhance employee engagement, commitment, and overall organizational effectiveness.